Chronic neutropenia in childhood: experience of a tertiary center - Letícia Matushita; Elvis Terci Valera; Davi Casale Aragon; Carlos Alberto Scridelli; Persio Roxo-Junior; Luciana Martins de Carvalho (Elsevier, 2024)
Objective: To assess the prevalence of chronic neutropenia (CN) and the clinical profile of patients with CN aged up to 18 years, followed in the pediatric hematology, rheumatology, or immunology outpatient clinic of a tertiary medical center from May 1, 2018, to 30 April 2019. Methods: Retrospective observational study carried out by collecting data from the patient's medical charts. CN was defined as absolute neutrophil count (ANC) below 1.5 × 109/L lasting over three months. Autoimmune neutropenia (AIN) was defined by clinical criteria and an over twofold increase in ANC after glucocorticoid stimulation. AIN was considered secondary when associated with autoimmune or immunoregulatory disorders. Wilcoxon and Fisher's exact tests were used to compare variables; the significance level was 5 %. Results: A total of 1,039 patients were evaluated; 217 (20 %) presented CN. Twenty-one (2 %) had AIN, classified as primary in 57 % of the cases. The average age at the onset of symptoms was 38.6 months. During follow-up, patients had 4.2 infections on average; frequency was higher among patients with secondary AIN (p = 003). Isolated neutropenia occurred in 43 % of the patients with AIN. Neutropenia resolved in eight (38 %) of the 21 patients with AIN within 19.6 months on average. Eight patients with secondary AIN met the criteria for Inborn Errors of Immunity. Conclusion: AIN prevalence was 2 %. Most cases were first evaluated by a pediatric immunologist or rheumatologist rather than a pediatric hematologist. This study highlights the need for a multidisciplinary approach involving a pediatric immunologist, rheumatologist, and hematologist.